PENGEMBANGAN PERANGKAT PEMBELAJARAN LISTRIK DINAMIS BERBASIS VIRTUAL EXPERIMENT UNTUK KULIAH TEORI DAN PRAKTIKUM TERINTEGRASI - Wayan Suana (UNIVERSITAS MUHAMMADIYAH METRO, 2017)
This development research aimed to produce effective virtual experiment-based learning tools of Electrodynamics topic for integrated Basic Physics II lecture of theory and practicum. Procedure development consists of four main stages, ie preliminary studies, product design, product development, and product validation. Learning tools developed included the syllabus and lesson plans, teaching materials, and student’s worksheets. The results of the expert assessment indicated that the product had a very good validity on the content aspects and a good validity on the design aspects. From the test results, it was found that the learning tools were effective to enhance student’s conceptual mastery of Electrodynamics. Thus, the product can be used as learning tools of integrated Basic Physics II course.